Hemodynamic performance of Trifecta: Single-center experience of 400 patients. (February 2015) - Modi, Amit; Budra, Mindaugas; Miskolczi, Szabolcs; Velissaris, Theodore; Kaarne, Markku; Barlow, Clifford W; Livesey, Steven A; Ohri, Sunil K; Tsang, Geoffrey M
Objective: To evaluate postoperative hemodynamic gradients and early outcomes of aortic valve replacement with the Trifecta bioprosthesis. Methods: Between 2011 and 2013, 400 patients underwent aortic valve replacement with a Trifecta bioprosthesis. Gradients were calculated by transthoracic echocardiography before discharge. Data were collected retrospectively; patients with postoperative severe left ventricular dysfunction or > mild mitral regurgitation were excluded. Results: The mean age was 75.9 ± 8.5 years, 197 (49.25%) patients were male, and 140 (35%) were >80-years old. Concomitant procedures were performed in 207 (51.75%) patients, and 30 (7.5%) had redo procedures. Supraannular aortoplasty with bovine pericardium was necessary in 25 (6.25%) cases. Hospital mortality was 2.75% (11 patients). Postoperative peak and mean gradients were 21.7 ± 9.3 and 11.1 ± 4.3 mm Hg for 19-mm valves ( n  = 29); 19.5 ± 7 and 9.7 ± 3.6 mm Hg for 21-mm valves ( n  = 158); 17.3 ± 6.6 and 8.7 ± 3.2 mm Hg for 23-mm valves ( n  = 134); 15.1 ± 6.1 and 7.8 ± 3.3 mm Hg for 25-mm valves ( n  = 56); 13.2 ± 3.7 and 6.9 ± 2.6 mm Hg for 27-mm valves ( n  = 11). Nine patients had trivial and one had mild transvalvular regurgitation. Mean follow-up was 1 ± 0.62 years; no patient required reoperation. Kaplan-Meier survival at 1 and 2 years was 94.3% ± 1.3% and 93.7% ± 1.4%. Conclusion: Early postoperative gradients are low after Trifecta implantation. Significant transvalvular regurgitation was not observed, but the incidence of supraannular aortoplasty may be increased.